1997
DOI: 10.1364/ol.22.000808
|View full text |Cite
|
Sign up to set email alerts
|

High-power continuous-wave upconversion fiber laser at room temperature

Abstract: We report cw laser emission of a Pr, Yb-doped ZrF(4)-BaF(2)-LaF(3)-AlF(3)-NaF fiber in the red spectral region. Laser emission was achieved on the transition P(0)(3)?F(2)(3)(lambda(L)=635 nm) with a Ti:sapphire pump laser tuned to lambda(p)=850 nm . A maximum output power of P(out)=675 mW was obtained at an incident pump power of P(in)=3.37 W . The output power was increased to P(out)=1020 mW when pumping with P(in)=5.51 W was provided by two Ti:sapphire lasers. A photon avalanche process was found to contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(85 citation statements)
references
References 13 publications
2
77
0
1
Order By: Relevance
“…The avalanche process is characterized by a nonlinear dependence of the upconversion fluorescence emission upon the pump intensity with the existence of a critical pumping threshold. 8,16,17 However, we have observed a slope decrease in the emission intensity for pump powers above 700 mW at 115°C, and 1.0 W at room temperature ͑20°C͒. This behavior is in agreement with the power dependence of the 3 P 0 population as will be demonstrated later on in this work.…”
Section: Resultssupporting
confidence: 91%
“…The avalanche process is characterized by a nonlinear dependence of the upconversion fluorescence emission upon the pump intensity with the existence of a critical pumping threshold. 8,16,17 However, we have observed a slope decrease in the emission intensity for pump powers above 700 mW at 115°C, and 1.0 W at room temperature ͑20°C͒. This behavior is in agreement with the power dependence of the 3 P 0 population as will be demonstrated later on in this work.…”
Section: Resultssupporting
confidence: 91%
“…Red, green, and blue laser sources pumped by IR lights at room temperature have been reported. [134] Wang et al [6] demonstrated a novel biosensor for the detection of trace amounts of avidin that is based on fluorescence resonant energy transfer between bioconjugated upconverted nanoparticles and gold nanoparticles. Liu et al [135] developed novel core-shell NaYF 4 :Yb,Er,Tm nanocrystals for intracellular imaging, and these nanocrystals are used for ratiometric sensing of H 2 S with high sensitivity and selectivity.…”
Section: Applicationsmentioning
confidence: 99%
“…Red and orange or green and blue upconversion lasing was observed. Sandrock et al [134] realized a highpower CW red radiation in a Pr 3+ /Yb 3+ -codoped ZBLAN fiber by tuning the wavelength of the Ti:sapphire pump laser to 850 nm. A maximum output power of 675 mW was obtained at an incident pump power of 3.37 W. When the fiber was pumped by two Ti:sapphire lasers at 852 nm and 826 nm, the highest output at 635 nm (1020 mW) so far was achieved.…”
Section: Upconversion Tmmentioning
confidence: 99%